Platform Kesehatan Kucing Dan Konsultasi Dokter Hewan - Fatmasari; Firdha Aprilyani; Romansyah, Ricky (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2024)
Abstract Cats are one of the most popular pets in Indonesia. However, it is important for cat owners to monitor their cats’ health because there is a possibility that they may suffer from infectious diseases. According to the National Center for Biotechnology Information, a study of 883 cats during 2010-2015 revealed that they were infected with several worrying diseases. Unfortunately, the uneven distribution of veterinarians throughout Indonesia is a challenge for cat owners. It is easier to find a veterinarian in urban areas, and other studies also show that cat owners are not always able to take their pets to the clinic due to busy schedules. As a result, many cat owners choose to self-treat their pets for minor illnesses, only visiting a clinic if the condition is severe.